Seed extract of Thai Mucuna pruriens reduced male reproductive damage in rats induced by chronic stress - Natthapol Lapyuneyong; Nareelak Tangsrisakda; Pannawat Choowong-In; Kowit Chaisiwamongkol; Nongnut Uabundit; Tarinee Sawatpanich; Supatcharee Arun; Alexander Tsang-Hsien Wu; Sitthichai Iamsaard (Taylor & Francis Group, 2022)
Context Thai Mucuna pruriens (L.) DC. var. pruriens (Fabaceae) (TMP) is known to enrich reproduction but preventive effects on stress related adverse reproductive parameters are not documented. Objective This study investigates the protective property of TMP seed extract on reproductive damage under chronic stress (CS). Materials and methods Male Sprague-Dawley rats were divided into four groups. The control and CS groups received distilled water, whereas the pre-treated rats received the aqueous TMP seed extract at doses of 150 and 300 mg/kg BW for 20 days before co-treatments with CS induction (immobilization and forced swimming) for 81 days. Serum was used to determine the cortisol and testosterone levels. Histology of testis and epididymis was observed with localization of androgen receptor (AR). Sperm parameters and the expression of steroidogenic acute regulatory (StAR), cytochrome P450 family 11 subfamily a member 1 (CYP11A1), AR, HSP70, caspases (3 and 9) and tyrosine phosphorylation (TyrPho) proteins were investigated. Results TMP extract improved cortisol level (0.84 ± 0.02 µg/dL) and protected against the damage of reproductive tissues and sperm parameters (count [49.78 ± 3.74 million sperm/mL], viability [90.01 ± 1.17%] and precocious acrosome reaction [1.38 ± 0.48%]). Expression of testicular StAR, CYP11A1, AR and HSP70 proteins was improved. Caspase expression was decreased in treated rats. TMP increased AR expression in CS sperm. Moreover, TyrPho protein expression was corrected after TMP administration. Conclusions TMP seed protected against adverse reproductive parameters in CS via improvements of functionally testicular markers and reductions of apoptotic proteins. It is possible to develop the TMP beans as an alternative medicine in treating of male subfertility caused by CS.